A TEACHER PERFORMANCE MANAGEMENT AT THE ISLAMIC CENTER FOUNDATION MADRASAH TSANAWIAH HIFZIL QUR’AN MEDAN ON COMPETENCY, MOTIVATION AND WORK DISCIPLINE - Tolib Harahap; M. Sjahril Effendi Pasaribu; Fahrizal Zulkarnain (Jurnal Ekonomi, 2022)
Teacher performance is the output or work results obtained by a teacher in carrying out the duties and responsibilities that have been attached to him. Good teacher performance can be measured through teacher professionalism which consists of mastering the four main competencies, namely professional, pedagogical, personal and social competencies. Pedagogic competence is a competency that must be possessed by a teacher in carrying out his duties and obligations. The research objective was to examine the influence of Competence, Motivation and Work Discipline on Teacher Performance in case studies at the Islamic Center Foundation for Madrasah Tsanawiyah Hifzil Qur'an Medan. The research population consisted of 80 people using saturated sampling. Data collection was carried out using the questionnaire distribution method and processed using the SEM – PLS data application. 3.0.